The Influence of Digital Communication on TikTok Addictive Behavior on Elementary School - Geofakta Razali; Yulianti Yulianti (Ikatan Sarjana Komunikasi Indonesia, 2022)
The rapidly advancing technology and the emergence of new media give a new color to communication especially internet-based digital communication. To interact without any limitations of space or time, the main characteristics of new media are their interconnectedness, their access to individual audiences as recipients and senders of messages, their interactivity, their diverse uses as an open character, and their ubiquitous nature. The daily life of human beings, ranging from children to the elderly, cannot be separated from the role of digital communication that shapes the character of addictive behavior which will be difficult to control. This study aims to examine the effect of digital communication on TikTok play addiction behaviour among the students of the Putra Kita Private Elementary School (SDS) in Menteng, Central Jakarta. This study uses a quantitative approach. This study is conducted by testing two variables between the independent variable Digital Communication X and the dependent variable Addictive Behavior Y. The population of this study were SDS Putra Kita students. The sample size of this study includes 80 respondents, who were taken using a random sampling technique. The entire population had the same opportunity to become a sample. The sample was randomly selected to be a respondent. Based on the analysis of the coefficient of determination (adjusted R2) the adjusted R2 = 0.638. This means that there is a contribution to Digital Communication in influencing addiction behavior by 63%.